Continuous training for Higher Education faculty. Case:Master’s in Production Engineering at UFRN - Desidério, Vanessa; Aloise, Dario José (Revista Gestão da Produção Operações e Sistemas, 2012)
This work aims to study the strategy found by a group of undergraduate teachers to be in constant develop-ment. It reasons about the creation and the stimulus of appropriated conditions for reading in a exhausting work routine and about the conciliation between teaching, research and extension activities of the graduate programme in production engineering. The work studies the permanent formation process of the teachers and the factors that restricts self-development according to the perception of those teachers. As methodology, the research was conducted as a case-study, by means of participation-observation, using documental search (data from curriculum lattes of the teachers was collected) and application of quantitative and qualitative questionnaires. The results indicate the possibility of improvement in the continuous learning process with the introduction of improvements in the infrastructure and the reading conditions presented by the teachers. This research might contribute to reflection about alternatives found by the teachers and the paradoxes with which they need to deal in order to overcome the challenges of continuous learning.Keywords: Permanent formation; Knowledge Management; Education in Production Engineering